Скіфські кургани між Чмиревою та Гаймановою Могилами (степова північна периферія Великої Білозерки) - Болтрик, Ю.В.; Шелехань, О.В. (Археологія і давня історія України, 2020)
У статті опубліовано матеріали зі скіфських курганів IV ст. до н. е., розкопаних у 1970 та 1972 рр. біля с. Велика Білозерка Запорізької обл. Розглянуті пам’ятки розташовані на давньому шляху, що відомий як Старий Чумацькій і був відгалуженням Муравського. Тут зафіксовано унікальні знахідки, які засвідчують потужний вплив античної культури на варварський світ. Серед матеріалів заслуговують на увагу зразки зброї та залишки прикрас: литик, золоті платівки та золота підвіска у вигляді об’ємного зображення голови Гери. Деякі риси поховального обряду уможливили звернутися до теми про ходи і лази в курганах. In 1970 and 1972 four Scythian Age barrows near Velyka Bilozerka village, Zaporizhia Oblast, were excavared. Barrow 2/1970. Two graves were discovered. One of them was totally looted. Another one was the tomb of the «archer» dated to the first half of the 4th century BC. It is notable due to the full quiver set where bronze, bone, and wooden arrowheads were combined. Barrow 1/1972. All Scythian Age graves were looted. Despite this fact, the barrow is interesting due to the dog burial in the ditch. Supposedly this dog had the role of the guard or guide between the worlds. Barrow 2/1972. It is a very noteworthy barrow. In the central grave 3 which is dated to the third quarter of the 4th century BC the unusual set of the gold appliquйs has been discovered. They have the images from the Greek mythology (Dionysus?), scenes of torment with lions and deer and scenes of opposed sphinxes, with the image of horned man. The unique masterpiece is the pendant in the shape of the female head in the high headwear (the Greek goddess Hera). In addition, in this grave the details of the heavy-armored warrior equipment: spearhead, javelin, scale armor, and bridle have survived. Barrow 3/1972. This late 4th century BC kurhan is interesting due to the catacomb with two dromoses. In addition, the gold appliquйs with images of the mythological creature that were interpreted as Bellerophon and Pegasus have been discovered here. Unique masterpiece is the glass intaglio with image of two fighting cocks. The kurhans under analyses were erected on the old trail that was known as Old Chumak Trail (branch of the Muravskyi Trail). Barrows 2/1972 and 3/1972, where most significant grave goods were found, could be interpreted as the tombs of the local kin leaders. Expressive materials show the strong impact of the Classic culture on the barbarian world in the 4th century BC.